The Moderating Effects of State Ownership and Duality on the Relationship between Internationalisation and Firm Performance: A Case Study of Listed Firms in Vietnam - Anh Que Tran; Dut Van Vo (Asian Academy of Management Journal, 2023)
This study was aimed at assessing the moderating effects of state ownership and chief executive officer (CEO) duality on the relationship between internationalisation and the performance of listed firms in the Hanoi Stock Exchange (HNX). A detailed panel data set of listed firms between 2009 and 2018 was analysed and the ordinary least squares (OLS) results revealed that the performance of high internationalising firms with high state ownership was higher than that of those with low or non-state ownership. In contrast, the performance of high internationalising firms governed by CEO duality was lower than that of those without duality. The findings integrate the arguments of the resource-based view and the Uppsala model applied in the transition economy that suggest internationalising listed firms acquire certain benefits from the state, and the separation of the highest two positions in such firms facilitates the exact anticipation of uncertainties and risks in making business decisions.